Learning Physical Education, Sports, and Early Childhood Health Based on Educational Games - Ruben Cornelius Siagian; Rizky Tri Wibowo; Dimas Imam Fadhilah; Putri Rahmadani Lubis; Ursulla Duti Oktria Simamora; M Abdurrahman Ridwan Isnan; Christeven Silalahi (Educational and Talent Development Center of Indonesia, 2022)
Physical education is an inseparable part of national education which aims to develop the abilities of students through physical activities. Physical education planning is carried out carefully to meet the behavioral development, growth, and needs of each child. Physical education not only develops psychomotor abilities, but also develops students' cognitive and affective abilities. Physical education learning starts early to start organic, motor, intellectual and emotional development. This study uses a descriptive qualitative approach by collecting and downloading an article or journal that conducts research directly in the field. The population in this study, which was taken from a journal, involved 3 teachers and 35 early childhood children, which was intended to obtain research results from the implementers and recipients of learning. Data collection techniques used open interviews, observation and documentation during the data collection process. The data analysis technique uses data reduction, data presentation and conclusion drawing which aims to provide research results that are in accordance with the reality in the field. Early childhood physical education currently shows complex problems, in terms of learning, facilities, social conditions and government policies. However, the purpose of education must be implemented properly to develop cognitive, affective and psychomotor abilities of early childhood. Nature-based educational activities are very suitable to be applied because apart from being able to practice corners during the pandemic, PAUD students can play comfortably and have fun.